Childhood Heritage Languages: A Tangier Case Study - Ariadna Saiz Mingo (Languages, 2025)
Through the testimony of a Tangier female citizen who grew up in the “prolific multilingual Spanish-French-Darija context of international Tangier”, this article analyzes the web of beliefs projected onto both the inherited and local languages within her linguistic repertoire. Starting from the daily realities in which she was immersed and the social networks that she formed, we focus on the representations of communication and her affective relationship with the host societies. The analysis starts from the most immediate domestic context in which Spanish, in its variant Jaquetía (a dialect of Judeo-Spanish language spoken by the Sephardic Jews of northern Morocco) was displaced by French as the language of instruction. After an initial episode of reversible attrition, we witnessed various phenomena of translanguaging within the host society. Following the binomial “emotion-interrelational space”, we seek to discern the affective contexts associated with the languages of a multilingual childhood, and which emotional links are vital for maintaining inherited ones. This shift towards the valuation of the affective culture implies a reorientation of the gaze towards everyday experiences as a means of research in contexts of language contact.